Does Price Matter in Charitable Giving? Evidence from a Large-Scale Natural Field Experiment - Karlan, Dean; List, John A (American Economic Review, 2007)
We conducted a natural field experiment to further our understanding of the economics of charity. Using direct mail solicitations to over 50,000 prior donors of a nonprofit organization, we tested the effectiveness of a matching grant on charitable giving. We find that the match offer increases both the revenue per solicitation and the response rate. Larger match ratios (i.e., 3:1 and 2:1) relative to a smaller match ratio (1:1) had no additional impact, however. The results provide avenues for future empirical and theoretical work on charitable giving, cost-benefit analysis, and the private provision of public goods. (JEL D64, L31)